Important parasitic zoonosis in dogs - Bresciani, Katia Denise Saraiva [UNESP]; Coelho, Willian Marinho Dourado [UNESP]; Coelho, Juliana de Carvalho Apolinário [UNESP]; Coelho, Natalia Marinho Dourado [UNESP]; Viol, Milena Araúz [UNESP]; Gomes, Jancarlo Ferreira [UNESP]; da Costa, Alvimar José [UNESP] (My University, 2012)
The dog can be involved in the mechanical transmission of infection by helminthes and protozoa; it has an epidemiological role in these zoonoses. The high rate of dogs naturally infected by endoparasites and the great possibility of acquiring this parasite justify the importance of attempting to prevent the occurrence of this illness. The aim of this paper is to demonstrate, through literature review, some clinical, epidemic and pathological aspects of endoparasite infection in the canine species. © 2012 Nova Science Publishers, Inc. All rights reserved.